IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING SEBAGAI UPAYA MEWUJUDKAN PEMBELAJARAN MATEMATIKA YANG AKTIF DI KELAS XII TIB SMK YAPPI WONOSARI - Kartika Budi Setyowati (JUSEDA, 2020)
This study aims to realize active mathematics learning in class XII TIB SMK YAPPI Wonosari using the Discovery Learning model. This type of research is Classroom Action Research. The subjects in this study were students of class XII TIB SMK YAPPI WONOSARI. The object of this research is the whole process and results of mathematics learning activities in improving the realization of active mathematics learning using the Discovery Learning model. The instrument in this study was active learning observation. This research was conducted in three cycles, the first cycle consisting of one meeting, the second cycle consisting of one meeting, and the third cycle consisting of one meeting. The data collection technique in this research is observation. Learning is carried out online through the Moodle-based Learning Management System (LMS), zoom meetings and WAG. This study shows that active learning has been achieved. This is indicated by an increase in the percentage of each active learning indicator from cycle I to cycle II and cycle III through observation. The observation results showed an increase in the percentage of active mathematics learning from cycle I to cycle II and cycle III, namely: Cycle 1 34.4%, cycle 2 41.13%, and cycle III 60.13%. Actions have reached the indicators of success in cycle III.